Contemporary trends in composite Ni-based catalysts for CO2 reforming of methane - Yusuf, M. (Elsevier Ltd, 2021)
The emission of greenhouse gases (GHGs), e.g. CO2 and CH4 into the atmosphere leads to an undesirable effect on climate change. One viable solution is to convert these two GHGs into valuable syngas via catalytic dry reforming of methane (DRM). Due to low-cost, feasibility, good catalytic activity, Ni-based catalysts have been used and tested extensively for DRM. However, the main limitation is the catalyst deactivation which occurs due to carbon formation and sintering of catalyst at high temperatures. This review aimed to provide up-to-date summary on the DRM process, including aspects of composite (bimetallic and trimetallic) catalysts and also the influence of doping metal on the catalysts. Furthermore, the metal support studies with the reaction mechanisms and kinetic studies, the latest catalyst configuration and their preparation methods have been highlighted. Therefore, the impending research focuses on composite catalysts and its density functional theory modelling for DRM to design an ideal catalyst. Â© 2020